2005
DOI: 10.1079/bjn20051460
|View full text |Cite
|
Sign up to set email alerts
|

The end-product method of measuring whole-body protein turnover: a review of published results and a comparison with those obtained by leucine infusion

Abstract: The present review summarizes the results of all published papers on whole-body protein turnover in man measured by [ The pros and cons of the two methods are compared and it is suggested that there is a place for further work by the less invasive end-product method, particularly for population studies of the genetic, environmental and functional determinants of whole-body rates of protein synthesis. Protein turnover describes the continual synthesis and breakdown of protein in the body. It is a fundamental bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 79 publications
2
54
0
Order By: Relevance
“…In contrast, 24-h rates of whole body protein turnover in the present study were equivalent to those measured in healthy free-living children utilizing similar methods (7); this is likely due to the incorporation of a fed-state period in the previous (7) and present studies, which would be necessary to elevate rates of protein turnover. In the present study, for example, rates of protein synthesis and protein breakdown as well as WBPB were greatest during the early 9-h exercise and recovery period, which is in agreement with the ability of exercise and protein feeding to increase whole body and muscle protein turnover in adults (11,14). The overnight fasted period, on the other hand, is characterized by lower rates of turnover and a net catabolism of lean tissue, which likely contributed to the attenuation in protein turnover and the subsequent WBPB when measured over 24 h in the present study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, 24-h rates of whole body protein turnover in the present study were equivalent to those measured in healthy free-living children utilizing similar methods (7); this is likely due to the incorporation of a fed-state period in the previous (7) and present studies, which would be necessary to elevate rates of protein turnover. In the present study, for example, rates of protein synthesis and protein breakdown as well as WBPB were greatest during the early 9-h exercise and recovery period, which is in agreement with the ability of exercise and protein feeding to increase whole body and muscle protein turnover in adults (11,14). The overnight fasted period, on the other hand, is characterized by lower rates of turnover and a net catabolism of lean tissue, which likely contributed to the attenuation in protein turnover and the subsequent WBPB when measured over 24 h in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, given the relatively small differences in protein intake between conditions, it is possible that if our intervention period persisted for a greater duration of time that rates of whole body protein turnover may eventually diverge between conditions. Alternatively, the sensitivity of oral [ 15 N]glycine may have precluded our ability to detect differences in protein turnover with the relatively small acute differences in protein intake between conditions that other methodology, such as intravenous infusions, may have permitted; however, discrepancies between measured rates of whole body protein kinetics by oral [ 15 N]glycine and [ 13 C]leucine infusion are more pronounced with measurements made in the fasted rather than fed state (14). Nevertheless, in general, whole body protein turnover (i.e., both synthesis and breakdown) is higher in children than adults and can be less sensitive to even large fluctuations in protein intake (19), which opens the possibility that even subtle changes in whole body protein synthesis and/or protein breakdown with exercise or nutrition could translate into physiologically more meaningful differences in WBPB because of these rapid rates of tissue remodeling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A label of the essential amino acid leucine has also been used to study whole-body protein metabolism during endurance exercise and a comparison between the glycine and leucine tracer techniques has been performed (54) . A stable isotope infusion of the branched-chain amino acid [1-13 C]leucine indicated that there was no difference in amino acid oxidation between rested, fasting endurance trained athletes when compared with age-, sex-and body weight-matched sedentary controls (55,56) .…”
Section: Exercise Tracer Studiesmentioning
confidence: 99%
“…The measurement of urea production via isotopic methods is often used as an estimate of net protein catabolism in those with an intact urea cycle [3,4,[13][14][15]. However, the application of metabolic tracers also has an important role in studying the urea cycle flux in patients with defects in the urea cycle.…”
Section: Introductionmentioning
confidence: 99%